On German-Croatian and Italian-Croatian Language Contact - Glovacki-Bernardi, Zrinjka; Jernej, Mirna (2004)
Croatia has always been a multilingual environment. The influence of German and Italian was empowered through direct political influence. During the second part of the 18th and in the 19th century native speakers of German and Italian used Croatian as a second language carrying out their duties at work. This bilingualism can tentatively be referred to as bureaucratic bilingualism. Native Croatian speakers used Italian and German as a second language in certain social areas. Such bilingualism can tentatively be called civic bilingualism. It can be assumed that starting with the 1960s civic German and Italian bilingualism no longer existed. Language contact within the daily life results in German and Italian loanwords in Croatian which are still actively present and used in daily communication.
ENG